2016
DOI: 10.1007/s00704-015-1727-0
|View full text |Cite
|
Sign up to set email alerts
|

Warm spells in Northern Europe in relation to atmospheric circulation

Abstract: This study describes warm spells in Northern Europe and determines the synoptic situations that cause their occurrence. In this article, a relatively warm day was defined as a day when the maximum temperature exceeded the 95th annual percentile, and a warm spell (WS) was considered to be a sequence of at least five relatively warm days. In the analysed multiannual period and within the investigated area, 24 (Kallax) to 53 (Oslo) WSs were observed. The occurrence of WSs was mainly connected with positive anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
3
12
0
1
Order By: Relevance
“…The increase in Tmax shown in the article was analogous to the results obtained for Central Europe, which were 0.52°C/10 years , and for Northern Europe, which were 0.38°C/10 years (Tomczyk, Piotrowski, Bednorz 2016). Similarly, in the research study of Twardosz and Kossowska-Cezak (2015) it was shown that the summer of 1974 in Arkhangelsk stood out against the period and was considered an extremely hot summer.…”
Section: Discussionsupporting
confidence: 79%
“…The increase in Tmax shown in the article was analogous to the results obtained for Central Europe, which were 0.52°C/10 years , and for Northern Europe, which were 0.38°C/10 years (Tomczyk, Piotrowski, Bednorz 2016). Similarly, in the research study of Twardosz and Kossowska-Cezak (2015) it was shown that the summer of 1974 in Arkhangelsk stood out against the period and was considered an extremely hot summer.…”
Section: Discussionsupporting
confidence: 79%
“…The recorded changes are similar to the ones mentioned in previous research studies conducted in the Iberian Peninsula, where the mean gain in warm days between 1950 and 2006 oscillated around 1.6% ± 0.3% days per decade [2] and was higher than the average increase in the global scale, which was 0.71% ± 0.35% days per decade [46]. The indicated changes are concordant with the ones occurring in Central [10], Northern [47] and Southern Europe [48]. Similar trends were shown by other authors carrying out their studies within particular countries, e.g., Czech Republic [49], Portugal [3], Serbia [8] and Ukraine [7].…”
Section: Discussion and Summarysupporting
confidence: 75%
“…in 1994, 2003, 2006, 2010, 2014 and 2015. As has already been shown in previous studies, their occurrence was associated with much larger anomalies of atmospheric pressure field and air temperature than on average during heat waves (Tomczyk 2016;Tomczyk, Piotrowski, Bednorz 2016;Tomczyk, Półrolniczak, Bednorz 2017;Tomczyk 2017).…”
Section: Discussion and Summarysupporting
confidence: 74%